Ferramenta computacional para geração distribuída a partir de sistemas híbridos renováveis - Machado, Rebeca Catunda Pereira (2014)
This work presents the development of a computational tool to aid in energy planning called GDHER (Distributed Generation of Hybrid Systems for Renewable Energy) The program can be used without cost since it was developed through the Calc a program of electronic spreadsheet similar to Excel which is part of a package of several free applications of Broffice After identifying some limitations of the main software available on the market we obtained a new tool adapted to the Brazilian reality especially to rural and isolated areas which uses the portuguese as language and has an interface very user friendly facilitating the understanding and operation of the program by the user The program allows the user to do the scaling of some methods of electricity generation from clean technologies such as solar photovoltaics wind turbines and biodigesters and through a financial analysis these systems are compared with the extension of the network of electric energy allowing the user get a prognosis of viability The tool also allows the user to do the scaling and the financial analysis of some configurations of hybrid systems like photovoltaic-wind photovoltaic-digester and wind-digester in order to find the optimal configuration for the project For validation of the program it was done a case study and from the financial analysis and sensitivity analysis the modality of electric energy supply more viable for individualized systems are the digesters then are the photovoltaic modules and the electrical network and finally are the wind turbines According to the financial analysis of hybrid systems the configuration more profitable is 75% of demand being served by biodigesters and 25% by photovoltaic modules The results are presented using tables and graphs for better understanding of the user With all these features the tool allows to scale systems with maximum efficiency and lower costs thereby obtaining more appropriate and reliable systems both from the technical point of view as financial